Sepsis Recognition and Early Intervention in Emergency Settings: A Life saving Approach - Saud Fahad Abdulmajeed; Abdulmajeed Hadi Alanazi; ‏‏Soja Shafiq Ali Al Naser; Ghufran Mohmmed Alobaid; Mufarreh Sultan Alsubaie; Mohammad Mosfer Alalyani; Mamdouh Farhan Raja; Meshal Saidan Awad Alshammari; Zahra Faisal Alsayegh (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Although medical care has advanced, sepsis is still a major worldwide health problem with millions of deaths each year. This is a condition wherein a systemic inflammatory response syndrome develops in the body to an infection and results in organ dysfunction and, in derogatory cases, multi organ failure. In the era of emergencies, with time being the deciding factor for patient outcome, identification and treatment of sepsis as expediently as possible are vital for survival. Aim of work: Toexplorethe importance of early recognition and timely intervention in the management of sepsis in emergency settings. Methods: We conducted a comprehensive search in the MEDLINE database’s electronic literature using the following search terms: Sepsis, Recognition, Early Intervention, Emergency Settings, Lifesaving and Approach. The search was restricted to publications from 2016to 2025 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:Early intervention in the emergency settings is essential to improve patient outcomes by reducing mortality from Sepsis. Successful sepsis management is highly associated with implementation of sepsis screening tools, adherence to the SSC bundle, and early initiation of fluid resuscitation and antibiotics. Yet, as challenges such as diagnostic uncertainty, ED overcrowding, and variability of adhering to protocols persist, proper care lags. Better recognition and intervention can be achieved through integration of AI driven sepsis alert system, clinicians training improvement and dedicated sepsis response teams. The focus should be to treat sepsis as an emergency so that many lives can be saved and the burden of sepsis related complications greatly diminished.